Electrochemical deposition and characterization of tungsten oxide as electrochromic films / Wan Danial Shahizuan Wan Ghazali - Wan Ghazali, Wan Danial Shahizuan (2016)
Tungsten oxide (WO3) has been extensively studied material for preparation of electrochromic film for smart windows applications. This work reports the preparation of WO3 films by electrodeposition technique. The effects of electrodeposition parameters such as deposition solution and deposition conditions on the structural, morphological and electrochromic properties of electrodeposited WO3 films were investigated. The deposited WO3 films were characterized using FESEM for surface morphology, ED AX for elemental analysis, XRD for structural properties, Cyclic Voltammetry for electrochromic performance and UV-Vis Spectroscopy for optical properties. The stability of bath solution containing tungsten ions from two different precursors (W salt and W powder) played an important factor in the formation of WO3 films on ITO-glass substrate. It was found that smooth, well adhered and transparent WO3 films with good electrochromic performances (switching colouration and cycling stability during intercalation and deintercalation of H + ions) can be prepared from 0.05M tungstate ions (using W powder) + lOmL H2O2 in the presence of 30 mL 2-propanol by applying constant potential of -0.45V vs Ag/AgCl for 300s at 40°C. Post-treatment by annealing has significantly changed the surface morphology and structural property of WO3 films from amorphous to crystalline after annealed at T > 300°C. The crystalline WO3 films have poor electrochromic performance than the amorphous films due to the entrapment of H+ ions into the crystalline structure of WO3 films. The coloured WO3 film has reflected about 70% the transmission of near-IR light (ie: solar heat). The prepared WO3 film is a great potential to be used as an electrochromic film in vehicles and building industries.